A comprehensive study on the incidence and management of incisional hernia - Malviya, Ajay; Patel, Arvind; Bhardwaj, Girish; Bulchandani, Hitesh P.; Saini, Vivek (International Surgery Journal, 2017)
Background: Incisional hernia is a frequent complication of abdominal surgery. The reported incidence of incisional hernia following abdominal surgery ranges from 2-20%. It may be caused by flawed operative techniques, by postoperative complications such as wound infection, by increased abdominal wall tension or by a metabolic connective tissue disorder. Methods: The present study was conducted on patients of incisional hernias admitted in various surgical wards of the department of surgery, associated group of hospitals attached to Dr. Sampurnanand Medical College, Jodhpur over a period of 10 years extending from 2005 to 2015. Detailed history and clinical examination of all patients were obtained from the case sheets. Other risk factors like obesity, hypertension, diabetes mellitus and malignant disease were recorded. Routine investigations were also documented. Patients were closely monitored in pre, intra and post-operative periods. The data collected were systemically recorded and statistically analysed. Results: Maximum incidence (67.21%) of incisional hernia seen in 31-60years of age and mean age was 48.54years with twice common in female sex. Abdominal swelling was the commonest (90.57%) presenting symptom. 80% of patients present within 1 year. Of previous surgery, 50% of them were gynaecological. Midline vertical incision (70%) was most notorious to develop in incisional hernia. Wound infection (50%) was major risk factor. Mesh repair (laproscopic 3.68% & open 92%) was the procedure of choice. Conclusions: Incisional hernia is twice common in women than in men with gynaecological procedures mainly caesarean section contributing for half of the cases of incisional hernias. It more frequently develops in vertical midline incision and post-operative wound infection is the most important predisposing factor. Incisional hernia usually appears within 1 year of previous operation. Mesh repair of incisional hernia has of late become popular amongst surgeons.